Posterior urethral hamartoma with hypospadias in a child: a case report and literature review - Hao, Zipeng; Zhanghuang, Chenghao; Zhang, Kun; Hang, Yu; Ji, Fengming; Yan, Bing; Tang, Haoyu (Frontiers in Pediatrics, 2023)
Abstract Background Hamartoma is a mass formed by the proliferation and disorder of two or more kinds of cells inherent in normal organs or anatomical parts, which can occur in any part of the body. The most common hamartoma are kidney hamartoma, spleen hamartoma, liver hamartoma, lung hamartoma, etc. Urethral hamartoma is extremely rare in clinical practice. Case Report Combined with literature review, the diagnosis and treatment process of a child with posterior urethral hamartoma and hypospadias in our hospital were analyzed. The patient was cured after surgical treatment, the lesion was completely removed, the appearance was satisfactory, and there was no recurrence, urethral stricture, urethral fistula and other complications. The pathological results of this case support the histological diagnosis of hamartoma, which provides reference for the clinical diagnosis and treatment of congenital malformation and tumor of urogenital in children. Conclusion When a child has posterior urethral hamartoma, the symptoms may not be very typical, and often combined with urethral malformation, need to be combined with careful physical examination and pathological diagnosis. Under normal circumstances, the prognosis of urethral hamartoma is good. However, in patients with urethral hamartoma, more cases need to be observed for verification, and long-term effective follow-up after surgery is needed.